Randomised controlled trial of an iPad based early intervention for autism: TOBY playpad study protocol. Issue 1 (December 2016) - Granich, Joanna; Dass, Alena; Busacca, Margherita; Moore, Dennis; Anderson, Angelika; Venkatesh, Svetha; Duong, Thi; Vellanki, Pratibha; Richdale, Amanda; Trembath, David; Cairns, Darin; Marshall, Wendy; et al.
Abstract Background Evidence for early intensive behavioural interventions (EIBI) by therapists as an effective treatment for children with an Autism Spectrum Disorder (ASD) is growing. High-intensity and sustained delivery of quality EIBI is expensive. The TOBY (Therapy Outcomes by You) Playpad is an App-based platform delivering EIBI to facilitate learning for young children with ASD, while enabling parents to become co-therapists. Intervention targets include increasing joint attention, imitation and communication of children with ASD. The primary aim of the study presented in this protocol is to determine the effectiveness of the TOBY App in reducing ASD symptoms when used as a complement to conventional EIBI. The secondary aim is to examine parental attributes as a result of TOBY App use. Methods and design Children aged less than 4;3 years diagnosed with ASD and parents will be recruited into this single-blind, randomised controlled trial using a pragmatic approach. Eligible participants will be randomised to the treatment group 'TOBY therapy + therapy as usual' or, the control group 'therapy as usual' for six months. The treatment will be provided by the TOBY App and parent where a combination of learning environments such as on-iPad child only (solo), partner (with parent) and off-iPad – Natural Environment (with parent) Tasks will be implemented. Parents in the treatment group will participate in a TOBY training workshop. Treatment fidelity will be monitored via an App-based reporting system and parent diaries. The primary outcome measure is the Autism Treatment Evaluation Checklist. The secondary outcome measures involve diagnostics, functional and developmental assessments, including parent questionnaires at baseline (T0), three months (T1) and six months (T2). Discussion This trial will determine the effectiveness of the TOBY App as a therapeutic complement to other early interventions children with ASD receive. The trial will also determine the feasibility of a parent delivered early intervention using the iPad as an educational platform, and assess the impact of the TOBY App on parents' self-efficacy and empowerment in an effort to reduce children's ASD symptoms. The outcomes of this trial may have EIBI services implications for newly diagnosed children with ASD and parents. Trial registration ACTRN12614000738628 retrospectively registered on 1st of July, 2014. UTN: U1111-1158-6423.